Człowiek i superbohater – Marvelowskie spojrzenie na Jana Pawła II - Kowalczyk, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The subject of interest in the paper is the comic book biography The Life of Pope John Paul II. In the 1980s, John Paul II was not only treated as the head of the Catholic Church, but held a place in popular culture. The article points out that the Marvel comic book was one of the works that positioned the Pope within an axiological community of superheroes who, in the most general perspective, showed what a life full of heroism should look like. Thus, the paper analyses the elements of the superhero rhetorical model and features typical of the comic medium that highlight the uniqueness of John Paul II’s biography. Furthermore, to fully reveal the persuasiveness of the creative solutions employed in this work, situating the Pope between a man and a superhero, the author refers to the analytical propositions of Roland Barthes and Michał Rusinek concerning the rhetoric of visual representations.